(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2024)
Hermetia illucens larvae, also known as the black soldier fly larvae, are best known as the decomposers of organic matter. There are many potential microbes found in the feces of BSF larvae. This research aimed to isolate the chitinolytic bacteria from chicken manure maggot waste, identify the antifugal activity, hydrolytic enzyme activity, phosphate and potassium solubilization, and bacterial species through 16S rRNA gene analysis. The initial screening focused on bacteria with chitinolytic ability. Antifungal activity tests were performed against phytopathogenic fungi, Colletotrichum sp. Isolate MKP02 showed the highest activity in inhibiting the growth of Colletotrichum sp. up to 100% and produced protease and cellulase enzymes, along with the ability to solubilize potassium. Furthermore, the potential isolate MKP04, the isolate shows the highest cellulolytic activity with a percentage of 300%. It can inhibit Colletotrichum sp. fungi, as well as having lipase enzyme content, and being able to dissolve potassium. The results of 16S rRNA gene amplification on the two isolates showed that both isolates were close to bacteria of the genus Lysinibacillus and Brevibacterium. This research is expected to provide valuable information about the bacterial content, levels of hydrolytic enzymes, and the ability to solubilize phosphate and potassium in BSF.